Inhibition of Rift Valley Fever virus using RNA interference technology - Scott, Tristan Alexander (My University, 2014)
Rift Valley fever (RVF) is a disease endemic to Africa, which has recently spread outside of Africa to the Arabian Peninsula. Rift Valley fever virus (RVFV) is the causative agent of RVF and manifests as severe hepatitis, encephalitis and haemorrhagic fever, resulting in mortality in approximately 1% of human cases. RVFV also affects agriculture as it causes high mortality rates in young ruminants (>90% in new-born lambs) and is associated with high levels of abortions, which results in devastating economic losses. RVFV is a single-stranded RNA virus with a genome comprising of three separate genetic elements referred to as the Large (L), Medium (M) and Small (S) segments. The negative sense L segment encodes an RNA-dependent RNA polymerase (RdRp) while the M segment encodes two glycoproteins, Gn and Gc, and two non-structural proteins, NSm1 and NSm2. The glycoproteins are important for viral entry, genome packaging and mature virion formation as well as being the main antigen for the elicitation of neutralising antibodies by humoral immunity. The NSm proteins are required for mosquito vector transmission and preventing viral-induced apoptosis in host cells. The ambisense S segment encodes in the positive orientation a non-structural (NSs) gene, and in the negative orientation the nucleocapsid (N) gene. NSs is an important virulence factor involved in subverting host defences and the loss of NSs results in a highly attenuated RVFV infection. N is required for RNA synthesis and encapsidation of viral genomes. There are currently very few treatments in the early stages of development and vaccines for RVFV are not readily available. The overall lack of therapeutic strategies for RVFV urges novel therapeutic development such as RNA interference (RNAi). Endogenous RNAi is triggered by dsRNA and is involved in gene regulation through sequence specific suppression of target mRNA. Therapeutic RNAi exploits the RNAi pathway to facilitate targeted degradation of viral genes and has been applied effectively to the inhibition of a number of viruses that cause chronic and acute infections. There are fewer studies that have used RNAi to inhibit highly pathogenic viruses. Efficacy has been demonstrated against Ebola virus, Lassa virus and Dengue fever virus, which suggests applicability to the inhibition of RVFV. In this thesis, short hairpin RNAs (shRNAs) were generated to target the NSs, N and M genes of RVFV, which are important proteins in the viral life cycle. To determine the knockdown efficacy of the shRNAs, HEK293 cells were transiently transfected with the shRNAs and a vector expressing the respective shRNA gene target fused to a luciferase reporter. The reporter levels were assessed using a dual-luciferase assay and several shRNAs were selected for further characterisation as a result of effective target knockdown. Consequently, the shRNAs reduced the levels of expressed FLAG-tagged NSs, N and M encoded proteins, which were detected using western blot analysis. ShRNAs directed against NSs were shown to disrupt this protein’s function to result in alleviation of pathogenic properties. Specifically, NSs was shown to suppress the transcription levels of a luciferase reporter as well as prevent the activation of an IFN-β promoter. When the shRNAs were transiently transfected into HEK293 cells, they were able to reverse NSs-induced suppression in the reporter assays. Furthermore, NSs is cytotoxic as determined by observing cell morphology under transmitted light microscopy, which was quantified using a MTT viability assay and cells that subsequently received anti-NSs shRNAs had improved viability. This class of anti-pathogenic shRNAs should be able to down-regulate NSs in vivo and attenuate RVFV virulence. However, NSs is not essential for viral replication and as a result of the aggressive pathology of haemorrhagic RVF, essential structural genes were targeted to investigate shRNAs with anti-replicative properties. ShRNAs directed against N were transfected 24 hrs prior to infection with RVFV. The inhibition of viral replication was determined by collecting supernatant over 3 days and measuring the levels of N antigen using an ELISA. The shRNAs demonstrated effective suppression of RVFV but N antigen was detected at 72 hrs post-infection, which suggested that the shRNAs were overwhelmed by the virus. A series of shRNAs against M were subsequently tested and the anti-M shRNAs effectively suppressed viral replication in cultured cells over an extended 96 hr experiment, demonstrating that M is a good target for RNAi-mediated inhibition of RVFV. In this thesis, the potential of RNAi-based therapeutics against RVFV was demonstrated and these data contribute to the growing knowledge that RNAi should be developed further as a potential treatment for haemorrhagic fever viruses. Finally, some DNA viruses such as HBV form cellular reservoirs from which new virus can be produced and the DNA is resistant to RNAi-mediated inhibition. RVFV is an RNA virus with an acute infection, which makes it more susceptible to RNAi and an excellent target for this particular therapeutic modality.
Keywords: Rift Valley fever (Disease) - Africa.; Communicable diseases - Africa.; RNA - Synthesis.